2006
DOI: 10.1111/j.1742-7843.2006.pto_543.x
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Azidothymidine‐Induced Cardiopathology in Mice by Mildronate, a Mitochondria‐Targeted Drug

Abstract: Azidothymidine, a nucleoside-analogue reverse transcriptase inhibitor (NRTI), is a commonly used antiretroviral drug in AIDS treatment, however its use is limited by severe toxic side effects due to its influence on mitochondria that result in myopathy, particularly affecting the cardiac muscle. We suggest that effective protection of azidothymidineinduced cardiopathology can be expected from drugs that are capable of targeting mitochondria. Therefore the present study in mice was carried out with mildronate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
3

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 24 publications
(32 reference statements)
2
18
0
3
Order By: Relevance
“…В третьих, ожидается, что любое потенциальное противодиабетическое средство будет применяться длительно, поэтому курс от четырех до шести недель, с одной стороны, будет максимально коротким, а с другой -достаточно долгим для предварительной оценки эффектов длительного лечения в модели на животных. Мы остановились на ежедневной дозе милдроната в 100 мг/кг, поскольку именно эта доза оказалась наиболее эффективной в ранее проведенных исследованиях [5,15,21] Влияние милдроната на порог невропатической боли. Как видно на рисунке 1, стрептозотоцин вызывал значительное снижение болевого порога примерно на 20% сразу после его первого введения.…”
Section: методикаunclassified
See 1 more Smart Citation
“…В третьих, ожидается, что любое потенциальное противодиабетическое средство будет применяться длительно, поэтому курс от четырех до шести недель, с одной стороны, будет максимально коротким, а с другой -достаточно долгим для предварительной оценки эффектов длительного лечения в модели на животных. Мы остановились на ежедневной дозе милдроната в 100 мг/кг, поскольку именно эта доза оказалась наиболее эффективной в ранее проведенных исследованиях [5,15,21] Влияние милдроната на порог невропатической боли. Как видно на рисунке 1, стрептозотоцин вызывал значительное снижение болевого порога примерно на 20% сразу после его первого введения.…”
Section: методикаunclassified
“…В изолированных митохондриях сердца крысы милдронат предотвращал повреждение митохондриального комплекса I азидотимидином, -препаратом, используемым против ВИЧ [14]. При моделировании кардиотоксического действия азидотимидина на мышах милдронат оказывал противовоспалительное действие, снижая клеточную инфильтрацию и экспрессию транскрипционного фактора NF-kBp65 в ядрах кардиомиоцитов [15]. Милдронат снижал также кардиотоксичное действие других анти-ВИЧ препаратов -ламивудина и ставудина [16].…”
unclassified
“…Nevertheless, since it is known that activation of MPT compromises the normal integrity of the mitochondrial outer membrane, thus influencing inner membrane leading to the release of cytochrome C, activation of caspase family proteins and subsequent apoptosis, as well as metabolic changes resulting in subsequent necrosis, 32 one may suggest that mildronate influences oxidative stress. Moreover, our previous data 10 obtained in mice cardiac tissue demonstrated that mildronate protected AZT-increased expression of redox-sensitive nuclear transcription factor kBp65 (NF-kBp65), which can be activated by reactive oxygen species, and plays a critical role in immune and inflammatory responses. 33 Other data showed that mildronate improved cardiac sarcoplasmic reticulum Ca 2þ uptake activity in rats with congestive heart failure following myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, for the present study we have chosen the model compound AZT, a well-known mitochondria-compromising anti-HIV drug. Previously, several studies have demonstrated that AZT causes changes in mitochondrial structure, alters respiratory chain enzyme activity, lowers mitochondrial ATP, activates reactive oxygen species, increases lactic acid production, and causes loss of mitochondrial DNA and cytochrome C. [28][29][30] Our previous experiments in AZT-induced cardiotoxicity model in mice, 10 as well as preliminary studies in neuroand hepatotoxicity states (unpublished data) demonstrated high anti-inflammatory and anti-apoptotic effects of mildronate, suggesting that it may regulate cellular damages initiated by AZT at least in part at the level of mitochondria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation